Pengaruh Media Sosial Sebagai Faktor Risiko dan Edukasi Terhadap Scam Online dalam Mempengaruhi Perilaku Konsumsi Mahasiswa di E-commerce: Studi Kasus Pada Mahasiswa di Bandung Raya - Putri Hasifah Rahmawati (Asosiasi Ahli Administrasi Indonesia, 2024)
The purpose of this study was to determine the effect of social media on online scams in influencing the consumption behavior of students in Greater Bandung. This study used 114 respondents as its sample using quantitative descriptive methods. The data analysis used is descriptive variable test, correlation test and regression test. The data from this study were obtained through distributing questionnaires in the form of Google Forms on social media and offline by face-to-face. This study shows that social media is able to influence online scams by 27.3%, then social media and online scams become two factors that can influence consumer behavior, each level of influence is 45.8% and 45.3%.